1992
DOI: 10.1111/j.1464-5491.1992.tb01835.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Inhibitory Polypeptide (GIP) Response in Diabetes Using a Highly Specific Antiserum

Abstract: Gastric inhibitory polypeptide (GIP), a hormone secreted from the proximal small gut, is recognized as a major component of the enteroinsular axis. However, circulating levels of GIP in diabetes have been reported to be exaggerated, normal or decreased following glucose ingestion, which may be due to the presence of variable crossreacting immunoreactive GIP forms in the circulation. We have raised an antibody (S705) which recognizes only 5 kDa GIP. Using this antiserum we have measured circulating GIP levels i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…1. Of the retrieved references, 22 (6,1030) (28 datasets) fulfilled our inclusion criteria (Supplementary Table 1). Total GIP was measured by antiserum R65 in 12 of the articles, by the ELISA kit (Millipore Corporation, Billerica, MA) in 7 articles, by the radioimmunoassay kit from (RIA kit; Phoenix Laboratories, Belmont, CA) in 2 articles, and by antibody S705, which recognizes 5-kD GIP, in 1 article.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1. Of the retrieved references, 22 (6,1030) (28 datasets) fulfilled our inclusion criteria (Supplementary Table 1). Total GIP was measured by antiserum R65 in 12 of the articles, by the ELISA kit (Millipore Corporation, Billerica, MA) in 7 articles, by the radioimmunoassay kit from (RIA kit; Phoenix Laboratories, Belmont, CA) in 2 articles, and by antibody S705, which recognizes 5-kD GIP, in 1 article.…”
Section: Resultsmentioning
confidence: 99%
“…Studies (6,1030) investigating adult patients with type 2 diabetes and appropriate healthy control subjects (weight-matched nondiabetic subjects) reporting plasma total GIP responses after oral glucose tolerance test (OGTT) or meal test were included. Data from studies that used early nonspecific assays (5,3139) were analyzed separately and were not included in the main meta-analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Different investigators using different RIA systems found normo-, hypo-and hyperGIPemia in type 2 diabetes [7][8][9][10][11][12][13][14]. Using the same assay system employing three different porcine GIP antisera, we have found hypo-and normoGIPemia in type 2 diabetes.…”
Section: Discussionmentioning
confidence: 83%
“…It is well established that circulating GIP consists of three immunoreactive GIP (IR-GIP) forms displaying variable immunoreactivity with different porcine GIP antisera [18,19], In this study, the use of ethanol extract of plasma in the assay system totally removed void volume IR-GIP, resulting in elimination of the variable contribution of this IR-GIP form [18]. It has been reported that a specific GIP antiserum for 5000 IR-GIP form did not show any difference in GIP responses in diabetes compared with a normal group [12]. Although variable cross-reactivity has been displayed by 8000 IR-GIP to most GIP antisera, it has been reported that 8 kDa GIP is not insulinotropic, even in pharmacological doses [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation